Construction of three-dimensional (3D) vertical nanosheets electrode with electrochemical capacity applied to microsupercapattery. (April 2022) - Ma, Qian; Wang, Shuaihao; Han, Xiaoxing; Cui, Jinlong; Jia, Guixiao; Zhang, Yongqiang; He, Wenxiu
Abstract: The preparation of heterostructure composites is regarded as an effective measure to enhance the electrochemical performances of pure component materials for energy conversion and storage. This paper reports a rapid microwave process to synthesize novel hierarchical multi-walled carbon nano-tubes and graphene nano-ribbons/Co–Ni LDH (MWGR/Co–Ni LDH) composites with superior performances in supercapattery. MWCNTs-GONRs with high conductivity, structural stability and electrochemical properties, and LDH with the construction of p-n junction are also profitable to transpire redox reaction. Thus, MWGR/Co–Ni LDH exhibites the distinctive heterostructure and splendid electrochemical properties (a high specific capacitance of 1030.2 C g −1 at 1 A g −1 ). In addition, the as-prepared MWGR/Co–Ni LDH//AC device performs the maximum energy density of 47.2 Wh kg −1 at power density of 0.85 kW kg −1 and good cycling performance of 88.8% retention after 10, 000 cycles at 10 A g −1 . Furthermore, the assembled asymmetric supercapattery (ACS) is adequate to provide energy for multiple lights emitting diodes (LEDs), which holds great promising practical applications for supercapattery. Highlights: MWGR/Co–Ni LDH nanosheets electrode with binder-free battery-like supercapattery device. MWGR/Co–Ni LDH shows a high specific capacitance of 1030.3 C g −1 at 1 A g −1 . DFT and capacitance contribution rate calculation of Co–Ni LDH and MWCNTs-GONRs. The MWGR/Co–Ni LDH//AC device shows high energy density and power density.